Analisis Keberhasilan Program UEP (Usaha Ekonomi Produktif) Melalui Model Context, Input, Process, Product (CIPP) di Kota Banda Aceh - Nasrullah Nasrullah; T. Lembong Misbah; T. Murdani (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2026)
The Productive Economic Enterprise Program (UEP) is an economic empowerment initiative designed to improve the welfare of low-income productive communities through household-based business development. In practice, its local implementation still faces challenges such as limited technical assistance, business sustainability, and market access. This study evaluates the effectiveness of UEP implementation in Banda Aceh City using the CIPP evaluation model (Context, Input, Process, Product). A qualitative evaluative approach was employed, with data collected through purposive interviews with 8 informants 2 Dinas Sosial staff, 2 TKSK officers, and 4 program beneficiaries supplemented by observation and documentation. Findings indicate that the program is contextually relevant to the needs of low-income communities; its input is supported by adequate policy foundations and organizational structures, although technical mentoring remains limited. The implementation process followed established procedures, while the product aspect demonstrated positive outcomes including increased household income, growth of productive micro-enterprises, and improved beneficiary independence. Comparative data across 2022–2024 show a decline in beneficiary numbers (22 → 12 → 6), suggesting a tightening of targeting criteria. Key challenges remain in product marketing and continuity of mentoring. Strengthening sustained assistance and developing a gampong-based empowerment ecosystem are critical to enhancing program sustainability.